Flavin Redox Bifurcation as a Mechanism for Controlling the Direction of Electron Flow during Extracellular Electron Transfer1. (26th August 2014) - Okamoto, Akihiro; Hashimoto, Kazuhito; Nealson, Kenneth H.
Abstract The iron‐reducing bacterium Shewanella oneidensis MR‐1 has a dual directional electronic conduit involving 40 heme redox centers in flavin‐binding outer‐membrane c‐type cytochromes (OM c‐Cyts). While the mechanism for electron export from the OM c‐Cyts to an anode is well understood, how the redox centers in OM c‐Cyts take electrons from a cathode has not been elucidated at the molecular level. Electrochemical analysis of live cells during switching from anodic to cathodic conditions showed that altering the direction of electron flow does not require gene expression or protein synthesis, but simply redox potential shift about 300 mV for a flavin cofactor interacting with the OM c‐Cyts. That is, the redox bifurcation of the riboflavin cofactor in OM c‐Cyts switches the direction of electron conduction in the biological conduit at the cell–electrode interface to drive bacterial metabolism as either anode or cathode catalysts.